2021
DOI: 10.1038/s41467-021-25796-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterising proteolysis during SARS-CoV-2 infection identifies viral cleavage sites and cellular targets with therapeutic potential

Abstract: SARS-CoV-2 is the causative agent behind the COVID-19 pandemic, responsible for over 170 million infections, and over 3.7 million deaths worldwide. Efforts to test, treat and vaccinate against this pathogen all benefit from an improved understanding of the basic biology of SARS-CoV-2. Both viral and cellular proteases play a crucial role in SARS-CoV-2 replication. Here, we study proteolytic cleavage of viral and cellular proteins in two cell line models of SARS-CoV-2 replication using mass spectrometry to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 83 publications
8
115
0
1
Order By: Relevance
“…However, no further biochemical or physiological validation was performed. In addition, Meyer et al (2021) very recently reported cleavage of NUP107 (Table 1) at position Gln 35 in SARS-CoV-2-infected A549-ACE2 cells and GOLGA3 at Gln 365 (Table S1), and ATAD2 at Gln 949 (Table 1), which we also found. In their study, GOLGA3 cleavage was elegantly validated in 3CL pro transfected cells, whereas NUP107 and ATAD2 cleavages were attributed to 3CL pro based on the cleavage logo but without direct evidence.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…However, no further biochemical or physiological validation was performed. In addition, Meyer et al (2021) very recently reported cleavage of NUP107 (Table 1) at position Gln 35 in SARS-CoV-2-infected A549-ACE2 cells and GOLGA3 at Gln 365 (Table S1), and ATAD2 at Gln 949 (Table 1), which we also found. In their study, GOLGA3 cleavage was elegantly validated in 3CL pro transfected cells, whereas NUP107 and ATAD2 cleavages were attributed to 3CL pro based on the cleavage logo but without direct evidence.…”
Section: Resultssupporting
confidence: 84%
“…We also demonstrate similarities and divergence at P2 from the dominant leucine specificity (Figure 1C) previously reported in the SARS-CoV-2 polyprotein (Scott et al, 2021), peptides (Rut et al, 2021), and monkey and human proteins (Koudelka et al, 2021;Meyer et al, 2021). In the polyprotein, P2-Val and P2-Phe each occur once.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…FOXP3 was also the only experimentally validated protein to be successfully predicted here. [18][19][20] This indicates that, as with 3CLpro prediction, any inaccuracies in prediction methods are amplified when applied to the entire human and must be experimentally verified, however enrichment analyses are robust against this variability. [1]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some endosome-targeting drugs may also act directly on viral glycoproteins ( 69 , 176 179 ), i.e., be both HTAs and DAAs. Other host factors to consider for targeting include host proteases that prime viral glycoproteins for fusion ( 37 , 38 , 119 , 120 ), other host proteins involved in virus entry ( 180 ), host cell kinases ( 181 184 ), and host proteins involved in viral RNA production ( 185 , 186 ), nuclear export ( 187 , 188 ), and virus assembly and egress ( 189 , 190 ). Given common viral infection strategies, the possibility exists for cross-family drug cocktails.…”
Section: Preparing For Other Emerging Virusesmentioning
confidence: 99%